Biomedical technology and devices - Moore, James E., Jr; Maitland, Duncan J. (CRC Press, 2013)
Biomedical Technology and Devices, Second Edition focuses on the equipment, devices, and techniques used in modern medicine to diagnose, treat, and monitor human illnesses. Gathering together and compiling the latest information available on medical technology, this revised work adds ten new chapters. It starts with the basics, introducing the history of the thermometer and measuring body temperature, before moving on to a medley of devices that are far more complex. This book explores diverse technological functions and procedures including signal processing, auditory systems, magnetic resona.
Keywords: Biomedical engineering -- Handbooks, manuals, etc.; Medical instruments and apparatus -- Handbooks, manuals, etc.; elektronické knihy; electronic books